Excitability of spinal neural function by motor imagery with isometric opponens pollicis activity: Influence of vision during motor imagery - Suzuki, Toshiaki; Bunno, Yoshibumi; Onigata, Chieko; Tani, Makiko; Uragami, Sayuri (NeuroRehabilitation (Reading, Mass.), 2014)
Background: No scientific basis exists for the effect of motor imagery with eyes open. Objective: To investigate spinal neural function during motor imagery and at rest with eyes open or closed by analyzing F-waves generated by the left thenar muscles after left median nerve stimulation. Methods: Sixteen healthy volunteers performed motor imagery while achieving 50% maximal voluntary contraction by isometrically contracting the opponens pollicis muscle. For subjective comparisons after the test, patients were asked whether imaging was easier with eyes open or closed and were then asked to imagine the contraction while holding the sensor between thumb and index finger with eyes open or closed. Results: Persistence during motor imagery under both visual conditions tended to increase compared with that at rest. F/M amplitude ratio was significantly higher during motor imagery under both visual parameters than at rest. Most subjects (14/16) found imaging easier with eyes open, but no relationship was found between F-wave data and subjective evaluations to determine the easier condition for motor imagery. Conclusion: Motor imagery with eyes open or closed increased the excitability of spinal neural output to the thenar muscles. However, subjective evaluation to determine the easier visual condition for motor imagery revealed insignificant results.